PERANCANGAN DAN IMPLEMENTASI SISTEM KEAMANAN JARINGAN SMART GRID - Rakhmadi Rahman; Putri Dyananda Luqman (Jurnal Riset Teknik Komputer, 2024)
In the era of digitalization, smart grids have become vital for efficient and sustainable energy distribution but are vulnerable to various cyber threats. This research aims to design and implement a robust network security system for smart grids to protect critical infrastructure from cyber-attacks. The methodology involves risk analysis, threat model development, and the application of advanced encryption and authentication technologies. The proposed security system incorporates multiple layers of protection, including firewalls, intrusion detection systems (IDS), and incident response mechanisms, supplemented by blockchain-based security protocols to ensure data integrity. Implementation results demonstrate that the system can effectively identify and counteract cyber threats, enhancing network resilience. Performance testing indicates that despite the additional security layers, the system operates within acceptable limits for latency and throughput. This research significantly contributes to the development of security standards for smart grids and provides practical recommendations for the industry in designing reliable and efficient security systems.